Dental students' knowledge level regarding the use of antibiotics in endodontic infections in pediatric patients - Dogan, Gizem Karagoz; Toptanci, Ismet Rezani (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Endodontic infections frequently occur in children and stand out as dental issues where antibiotics are widely favored. However, the recent overuse of antibiotics has resulted in the development of antimicrobial resistance in children. The awareness and understanding dental students have regarding the application of antibiotics for treating endodontic infections in pediatric patients have been explored in limited studies. Purpose: This study aims to evaluate the understanding of fourth- and fifth-year dentistry students—who are actively involved in patient care during their internships and will soon become medical professionals—about prescribing antibiotics to treat endodontic infections. Methods: This study was conducted using the Google Form electronic survey method on intern students at three different faculties of dentistry who have started their clinical internships. Results: Data were obtained from 468 participants who responded to the survey within the scope of the study. Statistically significant differences were observed in terms of knowledge level between those who were informed and those who were not about general antibiotic knowledge, prescription awareness, pediatric antibiotics dose calculations, and parenteral antibiotic applications, as well as between the places where they were informed; the same difference was observed between those who considered the information they received sufficient and those who did not (p < 0.05). Conclusion: The results of the study indicate that dental students have inadequate knowledge about the use of antibiotics in children with endodontic infections. Nevertheless, the study concludes that the knowledge level of the students can be improved through various training and educational programs.